The battle for international law : South-North perspectives on the decolonization era - Bernstorff, Jochen von; Dann, Philipp (Oxford : Oxford University Press, 2019)
This edited collection represents a comprehensive analysis of international legal debates between 1955 and 1975 related to the formal decolonization process, which brought a new perspective on topics such as self-determination, wars of national liberation, and multinational corporations.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 15, 2019).
Keywords: International law -- History -- 20th century